The Effectiveness of the Plan-Do-Check-Act (PDCA) Cycle in Managing the Anti-Bribery Management System at the Yogyakarta State Administrative Court - Icha Febi Hana Rohmatul Zhaza; Dewi Iriani; Tegar Bintang Aji Putra; Nabillah U. Khasanah; Ambarwati (CV. Cognispectra Publishing, 2026)
This study comprehensively examines the effectiveness of the Plan-Do-Check-Act (PDCA) cycle in managing the Anti-Bribery Management System (ABMS) at the Yogyakarta State Administrative Court. Using a qualitative descriptive approach, data were collected through in-depth interviews with key stakeholders, direct observation of the implementation process, and a review of relevant documents and policies. The findings indicate that consistent and structured implementation of the PDCA cycle has significantly improved organizational awareness and individual compliance with anti-bribery requirements. Through systematic planning, implementation, evaluation, and continuous improvement, the Yogyakarta State Administrative Court has strengthened its internal-control, monitoring, and evaluation mechanisms, thereby improving its capacity to identify, prevent, and mitigate bribery risks. However, several challenges continue to hinder optimization of the PDCA framework, including a shortage of competent human resources, organizational resistance to cultural change, and limited managerial commitment to sustaining the process.